Auto-feedback to improve academic performance - José Manuel Navarro Jover (OmniaScience, 2021)
This study was carried out on first-year engineering students in the subject of technical drawing, an eminently practical subject that requires the continuous development of spatial vision and also that students should devote time and effort to it from the very beginning. For the study we designed an auto-feedback activity to be applied to the students in the experimental group. The aim was to determine whether the students improved by this means their capacity for self-regulation and ultimately their academic performance. The students included in the experimental group obtained higher scores in the end-of-year self-regulation questionnaire (78.5) than those in the control group (66.47). There was a highly significant correlation (r=0.60; p<0.05) between the final grade and the class attendance rate. Although the auto-feedback treatment did not directly influence the final grades in the analysis of overall variance, it did have an indirect effect through the attendance variable; the students in the experimental group attended significantly more classes than those in the control group (82.2% vs. 68.6%; p<0.05). In fact, a comparison of the average final grades showed that the experimental group obtained significantly higher marks (6.97/10) than the control group (3.8/10).